La mise en œuvre de la loi 08-15 relative à l’achèvement et la mise en conformité des constructions inachevées dans la wilaya de Mila - Chebli, Nora; layeb, Hafid (Journal of Human Sciences, 2022)
Law 08-15 of July 20, 2008 laying down the rules of conformity of the constructions and their completion decreed with the aim of putting a term to a landscape urban dominated by unfinished dwellings, not in compliance with building permits, and to the anarchy that reigns in the field of construction and urban planning in Algeria.(Kheira Bachar, 2020).This article will try to provide some answers to the following questions : What is the nature of the constructions concerned and those excluded by the law 08-15 ? What are the town planning acts issued under this law, the issuance process, and the role of each stakeholder ? What are the obstacles, constraints and reasons for the rejections observed during the application of the law 08-15 and the results recorded during its implementation in the wilaya of Mila and at the national level ?